Learning from China? Manufacturing Investment and Technology Transfer in Nigeria - Yunnan Chen; Irene Yuan Sun; Rex Uzonna Ukaejiofo; Tang Xiaoyang; Deborah Brautigam (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
As China's economic boom has boosted domestic growth and income, higher wage costs are moving an increasing number of Chinese firms overseas. This presents a favorable opportunity for less developed countries in Africa and Asia to boost their export and manufacturing sectors, as well as opportunities to absorb Chinese industries seeking to reduce costs offshore. This paper examines new trends of Chinese foreign direct investment and technology transfer in Nigeria's manufacturing sector, and evaluates their potential to catalyze further industrialization in Nigeria. Fieldwork investigations of both Chinese and Nigerian firms in three regions of Nigeria show some evidence of positive, if limited, technology transfer, although they also reveal negative perceptions towards Chinese investment. While Nigerian economic policies have served to promote Chinese investment and skills promotion in Nigeria, a more coherent strategy is needed to leverage this new, growing source of capital and the potential resources it brings.
Keywords: 330